2023
DOI: 10.3390/antibiotics12061054
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Periprosthetic Joint Infection: The Utility of Biomarkers in 2023

Abstract: Periprosthetic joint infection (PJI) is a rare yet devastating complication following total joint arthroplasty (TJA). Early and accurate diagnosis of PJI is paramount in order to maximize the chances of successful treatment. However, we are yet to identify a single “gold standard” test for the diagnosis of PJI. As a result, the diagnosis of PJI is often challenging. Currently, the 2018 ICM definition of PJI is the only validated diagnostic criteria available. This article will review the importance of serum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…Therefore, this report proposes an analysis of the literature on the subject in a similar way to other recent studies that reviewed the diagnostic methods available for infections associated with implants and their advances, including an overview of sonication ( Birlutiu et al., 2017 ; Portillo and Sancho, 2023 ; Yilmaz et al., 2023 ; Azad and Patel, 2024 ). However, this review sought to analyze and describe the sonication protocols used in studies published in the last five years, with emphasis on the sensitivity and specificity rates achieved by these methods in comparison with PTC.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, this report proposes an analysis of the literature on the subject in a similar way to other recent studies that reviewed the diagnostic methods available for infections associated with implants and their advances, including an overview of sonication ( Birlutiu et al., 2017 ; Portillo and Sancho, 2023 ; Yilmaz et al., 2023 ; Azad and Patel, 2024 ). However, this review sought to analyze and describe the sonication protocols used in studies published in the last five years, with emphasis on the sensitivity and specificity rates achieved by these methods in comparison with PTC.…”
Section: Introductionmentioning
confidence: 98%
“… 5 In addition, various synovial fluid and blood indices, imaging examinations and metagenome sequencing also have great significance for the diagnosis. 6 The bacterial biofilm attached to the prosthesis is one of the important reasons for the formation of chronic infections due to its resistance to antibiotics, immune system, and mechanical debridement. 7 Some immunosuppressive factors (such as PD‐L1) may play an important role in the formation of the immunosuppressive microenvironment in the joint capsule.…”
Section: Introductionmentioning
confidence: 99%
“…Serum erythrocyte sedimentation rate (ESR) and serum CRP can be affected by various systemic inflammatory conditions such as autoimmune disorders, obesity, non-joint-related infections, and others. In contrast, alpha-defensin determination remains accurate even in the presence of antibiotics and blood admixtures in the synovial fluid, but is costly and has limited accessibility, and studies have shown that it is not statistically superior to the combination of the WBC count and the PMN% in the synovial fluid [13,15]. Research into new reliable biomarkers for the diagnosis of PJI is ongoing, focusing on some new markers such as procalcitonin [16], calprotectin [17], IL-1β [18], and other immune system-related proteins.…”
Section: Introductionmentioning
confidence: 99%